PENGARUH KOMPETENSI DAN KOMPENSASI TERHADAP MOTIVASI BERPRESTASI DALAM MENINGKATKAN KOMITMEN ORGANISASIONAL PANITIA PENGADAAN BARANG/JASA STUDI DI SATUAN KERJA KEPOLISIAN DAERAH (POLDA) JAWA TENGAH (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study aimed to examine the effect of competence and compensation to organizational commitment through achievement motivation in personnel who already have the certification of the procurement of goods and services in the Central Java Police Headquarters. Population of 100 people, with census sampling technique, so that the total sample of 100 people. Analysis using: test the validity of the factor analysis (KMO> 0.5), reliability testing with Chrombach Alpha (Alpha Chrombach> 0.6), the model test with Adjusted R2 and F-test, hypothesis testing with multiple linear regression and t test (t count> 0,05).The results: competence and compensation a positive effect on organizational commitment, and competence and compensation directly influence organizational commitment without mediation through achievement motivation. Keywords: competence, compensation, organizational commitment, achievement motivation